KESIAPSIAGAAN MASYARAKAT DALAM MENGHADAPI SITUASI BENCANAGUNUNG API SEULAWAH AGAM DI WILAYAH KECAMATAN SAREE KABUPATENACEH BESAR - Nita Adlina; Agussabti .; Hermansyah . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2014)
Abstract: Disaster is a serious disruption of the functioning of a society, causing widespreads loss of human life, in terms of economic, social function and environmental. This study aims to determine the level of community preparedness for disaster situations of Seulawah Agam Volcano, Saree sub-district area of Aceh Besar regency. This disaster education research uses a quantitative approach with crossectional design. The research was held on 15th until 31st December 2013. Population in this study is all the people who never get a disaster simulation of Seulawah Agam Volcano, Saree Sub-district area of Aceh Besar Regency which amount 226 of people consisted of men and women. The obtaining sampel was conducted by 69 of people. The sampling technique in this research were calculated using random sampling . The results showed the Preparedness of Ready by 29 people ( 42. 0 % ), Knowledge To know that as many as 27 ( 39. 2 % ), Information systems that are Less known, as many as 31 ( 44. 9 % ) compared with only 20 information known ( 28. 9 % ), the vulnerability was poor, as many as 30 ( 43. 5 % ), the Attitude was Enough as many as 32 ( 46. 4 % ), frekusensi of the Simulations in Seulawah Agam Volcano disaster situations who Do not understand as many as 29 ( 42. 0 % ). Regional Disaster Management Agency ( BPBD ) of Aceh Besar is suggested to perform continuous education about the dangers and signs of a volcanic eruption to the community, especially people who have dwellings around the volcanic eruption. Keywords : Preparedness, Volcanic eruptions. risk